(untitled) (Tanzania Medical Journal, 2022)
Tanzania Medical Journal is proud to be collaborating with the Organizing committee of the 3rd National Non-Communicable Diseases Scientific Conference in publishing the abstracts presented at the conference that was held on 11th - 12th November 2021, at the Arusha International Conference Center, Arusha, Tanzania. The conference theme was: “Multisectoral Engagement and Collaboration in addressing Non-Communicable Diseases”. The abstracts are listed along with authors’ affiliations. The scientific committee for this conference was responsible for peer review of the abstracts.